Settings On The Age Limit for Nomination as Regional Head or Deputy Regional Head in The Regional Government System in Indonesia - Mareta, Moch. Firmandika Gita; Harimurti, Yudi Widagdo; Zaman, Nurus (Journal of Law, Politic and Humanities, 2025)
The direct election of regional leaders, as mandated by Article 18(4) of the 1945 Constitution, aims to produce leaders with competence, integrity, and dedication in line with the people’s aspirations. However, debates have emerged regarding the correlation between young or new leaders and their performance, which has sparked discussions on revising candidate requirements, particularly age limits. This study examines (1) how the age limit for regional head and deputy nominations is regulated in Indonesian law, and (2) the reasons behind changes in these requirements. Using a normative legal research method with statutory and conceptual approaches, the study finds that Law Number 10 of 2016 sets the minimum age at 30 years for governor and deputy governor candidates, and 25 years for mayor, deputy mayor, regent, and deputy regent candidates. Following a Supreme Court decision (Case No. 23 P/HUM/2024), the age requirement is calculated based on the swearing-in date. The Constitutional Court emphasizes that Article 7(2)(e) of Law No. 10 of 2016 must be strictly applied during the nomination process. Furthermore, the amendment of age limits cannot be separated from potential conflicts of interest among office holders. Constitutionally, such amendments are legitimate, whether conducted through judicial, legislative, or executive review.